2017
DOI: 10.1111/apa.13908
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum 25(OH)D concentration is associated with lower risk of chronic otitis media with effusion: a case-control study

Abstract: This finding supports further investigation into whether the risk of COME could be reduced by increasing serum 25(OH)D concentration through increased sun exposure, higher dietary intake or vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
(40 reference statements)
0
11
0
2
Order By: Relevance
“…Several clinical studies indicate that low vitamin D status is significantly associated with a high risk or severity of OM [ 12 13 14 15 ]. A recent case-control study by Cayir et al [ 12 ] showed that the mean serum 25(OH)D level was significantly lower in children with recurrent OM compared with controls (28.5 nmol/L vs. 72.9 nmol/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies indicate that low vitamin D status is significantly associated with a high risk or severity of OM [ 12 13 14 15 ]. A recent case-control study by Cayir et al [ 12 ] showed that the mean serum 25(OH)D level was significantly lower in children with recurrent OM compared with controls (28.5 nmol/L vs. 72.9 nmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies reported a significant association between vitamin D status and OM [ 12 13 14 15 ]. However, little is known about the role of vitamin D status in the pathophysiology of OM.…”
Section: Introductionmentioning
confidence: 99%
“…Some stronger evidence comes from a case control study where the higher serum 25(OH)D concentrations, with or without supplementation, were associated with a lower risk of chronic otitis media with effusion (COME) in preschool children. They proposed that COME could be reduced by increasing serum 25(OH)D concentration through increased sun exposure, and higher dietary intake or vitamin D supplementation [52]. A more recent study strongly suggests that there is a significant association between vitamin D deficiency and follow-up outcomes of OME, as well as a strong effect of vitamin D on OME prognosis [53].…”
Section: Otitis Mediamentioning
confidence: 99%
“…Введение 1000 МЕ/сут витамина D восстанавливает значения D 25 (OH) в сыворотке крови до ≥30 нг/мл, и в большинстве случаев это приводило к значительному снижению риска возникновения ОСО [32]. По данным одного из последних клинических наблюдений выявлено, что низкий уровень 25-гидроксихолекальциферола предрасполагает к возникновению персистирующего течения экссудативного среднего отита, что является важнейшим предрасполагающим фактором к возникновению рецидивирующих острых средних отитов [33].…”
Section: бронхопульмонология и лорunclassified